On improving NLO merging for t t ¯ W $$ t\overline{t}W $$ production - Rikkert Frederix (SpringerOpen, 2021)
Abstract We introduce an improvement to the FxFx matrix element merging procedure for pp → t t ¯ W $$ t\overline{t}W $$ production at NLO in QCD with one and/or two additional jets. The main modification is an improved treatment of jets that are not logarithmically enhanced in the low transverse-momentum regime. We provide predictions for the inclusive cross section and the t t ¯ W $$ t\overline{t}W $$ differential distributions including parton-shower effects. Taking also the NLO EW corrections into account, this results in the most-accurate predictions for this process to date. We further proceed to include the on-shell LO decays of the t t ¯ W $$ t\overline{t}W $$ including the tree-level spin correlations within the narrow-width approximation, focusing on the multi-lepton signatures studied at the LHC. We find a ∼30% increase over the NLO QCD prediction and large non-flat K-factors to differential distributions.